Using semantic mapping and reading comprehension skills, among ninth graders at a public institution in Loja, during the 2022-2023 school year - Pardo Malacatus, Juliana Nohemí (2023)
Reading comprehension skills are fundamental in the EFL students' learning because it permits students to grasp the central message of the written texts. This study focused on using three semantic mapping strategies such as story, mind and concept mapping to improve students' reading comprehension skills. For that reason, it aims to answer the main objective about to improve the reading comprehension skills by using semantic mapping, among ninth graders at a public institution in Loja, during the 2022-2023 school year, and as specific objectives (1) to identify the effectiveness of using semantic mapping on the improvement of reading comprehension skills, and (2) to describe the students’ perceptions about using semantic mapping on the improvement of reading comprehension skills. This study used a mixed method to collect quantitative and qualitative data by administrating pretest, posttest, mixed questionnaire and using field notes as instruments, which were applied to 40 ninth graders from a public institution being selected by convenience sampling. This study also utilized Gerald Susman action research cycle which consists of five steps, and it helped the researcher to be clear about the order and progress of the research. The pretest and post test results indicated that there was a significant increase in students' reading comprehension skills because students improved on identifying main ideas, details, summarizing and making inferences. The results of the questionnaire showed that students had positive comments in relation to the usage of the three types of semantic mapping to improve reading comprehension skills. Finally, the research concluded that the implementation of semantic mapping was effective in students' reading comprehension skills improvement being positive on students' performance. Keywords: improvement, reading comprehension skills, semantic mapping